Clinical outcomes of cases with missing lateral incisors treated with the ‘T’-Mesialslider - Kanavakis, Georgios; Ludwig, Björn; Rosa, Marco; Zachrisson, Bjorn; Hourfar, Jan (Journal of orthodontics, 2014)
The objective of this article is to review the fabrication and activation procedures of the ‘T’-Mesialslider and to present the clinical outcomes in cases where canine substitution is the treatment of choice for missing maxillary lateral incisors. The ‘T’-Mesialslider allows for effective mesial translation of the canines and the posterior dentition, without significant loss of anterior anchorage and with good vertical control. Possible adverse effects of the appliance and clinical recommendations for their management are also discussed. In canine substitution cases with high anchorage demands, the ‘T’-Mesialslider provides an effective treatment option.